Studi Kinerja Relay Proteksi pada Transformator II 150/20 KV 50 MVA dengan Penyulang Lakarsantri di GIS Karangpilang PT. PLN (Persero) UPT Malang ULTG - Riska Salsabila Sugiarto; Ummu Hanik; Budi Eko Prasetyo; Rhezal Agung Ananto (UPT - P2M POLINEMA, 2021)
The substation is one of the components of the electric power system that is an important role in the distribution ofelectrical energy and load regulation. In the process of distributing electrical energy, continuity of good service is needed, but theinterferences still often occur, both internal and external. On Sunday, July 21, 2019 there was an interference, Lakarsantri feeder CB failed to trip so make the incoming 20kV CB trip. That interference was caused by the burning of the Switching Substation in the Citraland area. Therefore, a new relay setting is needed as a recommendation to use transformator 2 to avoid the recurrence of a similar fault. The relay settings have shown good results where the working time of the relay on the outgoing feeder side is faster than the incoming feeder 20kV and the incoming transformator 150kV side, when coordination simulated using the E-TAP 12.6.0 software by entering the current setting and the time setting, it shows good coordination because when there is an interference on the outgoing feeder, CB outgoing feeder works first, not the incoming feeder 20kV CB or the incoming transformator 150kV CB. Preventive maintenance on other equipment such as CB and CT need to be be done to increase of equipment reliability to reduce the occurs of protection failure or damage to the equipment.